MICRO-DEFORMATION BEAM’S CONSTRUCTION DESIGN AND OPTIMIZATION ON VERTICAL FORCE LOADING - CHENG HaiYing; SHI Tou; YANG Tao (Jixie qiangdu)
Designing large-span and micro-deformation load bearing crossbeam for the vertical loading force. the designing span of Crossbeam is 3422 mm. Horizon displacement is 1100 mm. Reruirement crossbeam’s deformation amount less 50 μm.when loading vertical force in the destination of working plane. Using the steel with the thickness of 16 mm as the main material,imitating I-steel’s strong compressive behavior and equal intensity beam anti-deformation ability to design coincidence working condition’s non-standard microdeformation and soft Weight crossbeam,making it to reach design deformation amount and allowable stress by ANSYS Workbench. Using the crossbeam’s total deformation and equivalent stress tiny as the objective function,imitating I-steel and equal intensity beam’s key structures which is P3,P4,P5,P6 as the design variable to optimize the crossbram structure. Through the vertical loading force experimental analysis for non-standard crossbeam,the system maximum deformation is 38 μm when the loading force is 10 k N,ANSYS Workbench solving is 40 μm,the relative error is 5% of them,crossbeam meets the conditions required by optimization.